The relatton between fleece losses and ztnc, copper levels in blood serum of merino sheep in karacabey state farm flock - Sema OZAN (Eurasian Journal of Veterinary Sciences)
The aim of this study was to determine the relation between fleece losses and Zinc, Cupper levels in blood serum of Merino Sheep. Thirty fleece lossed and fourty two healthy Merino Sheep in Karacabey State Farm Flock were used as material. The average levels of Zinc and Copper in blood serum of healthy ,Merino Sheep .group were;